Carbon Stock Potential across Different Land Covers in Tropical Ecosystems of Damota Natural Vegetation, Eastern Ethiopia - Abdulbasit Hussein (Applied and Environmental Soil Science)
The research was carried out in Damota kebele, in the Oromia regional state of Ethiopia, to examine the carbon sequestration potentials under three land covers (i.e., farmland (FL); bushland (BL), and woodland (WL)). In the three land covers, 60 squares of 20 m × 20 m, 5 m × 5 m, and 1 m × 1 m with six horizontal transect lines were employed to gather data on tree, shrub, herbaceous, and soil, respectively. To estimate organic carbon percentage, soil parameters were collected from three soil profiles (i.e., 0–10 cm, 10–20 cm, and 20–30 cm). The results showed that MA had significantly higher above-ground carbon (AGC) with 67.9 ± 11.4 Mg ha−1, whereas BL had significantly higher below-ground carbon (BGC) stocks with 16.32 ± 5.5 Mg ha−1, compared to other gradients. However, FL had the lowest AGC (53.2 ± 4.5 Mg ha−1) and BGC (8.04 ± 2.9 Mg ha−1). FL exhibited a significantly higher SOC value than the other two land covers followed by WL. The BL had the lowest SOC value. SOC across the three soil profiles follows a reduction trend from topsoil depth to lower soil depth with significant variation. WL had relatively higher TC than the other gradients. But FL had the lowest TC stock. Due to a high amount of human and animal interference in FL, weak security, and law enforcement measures, it has low TC. In conclusion, FL should embrace the better ecological, policy, and socioeconomic considerations than the other land covers.